Electrochemical cell design with polymer composite layer
By using a polymer composite layer to isolate lithium metal anode and liquid electrolytes in lithium metal batteries, the problem of incompatibility between lithium metal anode and liquid electrolytes is solved, and a battery unit design of high -energy density and long -cycle life is realized.
Patent Information
- Application Number
- CN202411004092.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2023-07-27
- Filing Date
- 2024-07-25
- Publication Date
- 2025-01-28
AI Technical Summary
The lithium metal anode is incompatible with commonly used liquid electrolytes, resulting in uneven lithium plating and low energy density, limiting the application of lithium metal batteries.
A electrochemical battery unit is designed. The polymer composite layer isolates the lithium metal anode to isolate from the liquid electrolyte. The polymer composite layer consists of the cross -linking polymer main chain, polyethylene glycol, polycopide, and lithium salt to provide provided to provide provided to provide it. Improved hole control, ion conduction, and diaphragm binding strength.
A dense and uniform lithium coating is achieved, the volume energy density and weight energy density of the battery unit is improved, the cycle life is prolonged, and external pressure clamps are not required.
Smart Images

Figure CN119381504A_ABST
Abstract
Description
Technical Field
[0001] The present disclosure relates to an electrochemical cell design using a high energy density lithium metal anode and having a polymer composite layer between the cathode and the lithium metal anode. Background Art
[0002] Lithium metal batteries have received great attention as advanced high-performance next-generation batteries. Lithium metal batteries are attractive because of their high volumetric energy density and weight energy density. However, lithium metal anodes are incompatible with liquid electrolytes commonly used in lithium-ion battery cells, resulting in large irreversible anode volume increases due to insufficient electrochemical reversibility, resulting in low energy density and low cycle life, respectively. Modifying the composition of the liquid electrolyte may not lead to a feasible battery cell design because the lithium metal anode still reacts with the liquid electrolyte and forms an uneven and fluffy lithium plating. The direct contact between the liquid electrolyte and the lithium metal anode leads to a continuous reaction at the lithium metal interface, which consumes the liquid electrolyte and forms an unfavorable solid electrolyte interface (SEI) layer. The loose contact between the lithium metal anode and the separator allows fluffy lithium dendrites to grow into the liquid electrolyte space. Other factors such as uneven current distribution at the lithium metal interface are particularly attributed to uneven and fluffy lithium plating at high current rates. The resulting structural instability limits the application of these batteries. Applying external pressure to try to limit the thickness growth of the lithium metal anode will not eliminate the dendritic fluffy morphology, and is unfavorable or unfeasible in many practical applications. Summary of the invention
[0003] Disclosed herein are embodiments of an electrochemical cell design comprising a cathode, a lithium metal anode, a separator between the cathode and the lithium metal anode, a liquid electrolyte, and a polymer composite layer bonding the lithium metal anode to the separator. The polymer composite layer comprises a cross-linked polymer backbone, polyethylene glycol, polycaprolactone, and one or more lithium salts.
[0004] Also disclosed herein is a manufactured electrochemical cell having a cathode having a cathode current collector and a cathode active material; an anode comprising an anode current collector, lithium metal on the anode current collector, and an anode cap layer on the lithium metal opposite the anode current collector. The anode cap layer is composed of one or more metals, at least one of the one or more metals being alloyed with the lithium metal. The electrochemical cell also has a separator between the cathode active material and the anode, a liquid electrolyte, and a polymer composite layer bonding the anode cap layer to the separator. The polymer composite layer is composed of a cross-linked polymer backbone, polyethylene glycol, polycaprolactone, and one or more lithium salts.
[0005] Also disclosed is a lithium metal battery comprising one or more electrochemical cells as disclosed herein, wherein the lithium metal battery has an external operating pressure of 20 psi or less. BRIEF DESCRIPTION OF THE DRAWINGS
[0006] The following detailed description is best understood in conjunction with the accompanying drawings when reading this disclosure. It should be emphasized that, according to convention, the various features of the drawings are not to scale. On the contrary, the sizes of the various features are arbitrarily enlarged or reduced for clarity.
[0007] Figure 1 is a schematic diagram of an electrochemical cell design as disclosed herein.
[0008] Figure 2 is a scanning electron microscope / energy dispersive X-ray spectroscopy (SEM / EDS) image of a surface having only a polymer backbone layer of polyethylene glycol.
[0009] Figure 3 is a SEM / EDS image of a surface having only a polymer backbone layer of polycaprolactone.
[0010] Figure 4 is a SEM / EDS image of the surface of a fabricated polymer composite layer as disclosed herein with 17.0 wt % lithium salt.
[0011] Figure 5 is a SEM / EDS image of the surface of a fabricated polymer composite layer as disclosed herein having 34.0 wt % lithium salt.
[0012] Figure 6 is a graph comparing the crystallinity of various polyethylene glycols, polycaprolactones, and both polyethylene glycol and polycaprolactone with a polymer backbone and with the polymer backbone alone.
[0013] Fig. 7A and Figure 7B is a graph comparing the tensile strain and stress of polymer composite films containing various polyethylene glycols, polycaprolactones, and both polyethylene glycol and polycaprolactone blended with a polymer backbone and the polymer backbone alone. DETAILED DESCRIPTION
[0014] Although lithium metal batteries are attractive due to their high volumetric and gravimetric energy densities, lithium metal anodes are incompatible with conventional liquid electrolytes used in lithium-ion battery cells. This incompatibility results in uneven lithium plating and fluffy lithium plating, resulting in performance issues that can limit the application of these batteries. Uneven and fluffy lithium plating can be caused in part by: 1) contact between the liquid electrolyte and the lithium metal anode, which results in continuous reaction at the lithium metal interface, thereby consuming the liquid electrolyte and forming an unfavorable SEI layer; 2) loose contact between the lithium metal anode and the separator, which allows fluffy lithium dendrites to grow into the liquid electrolyte space; and 3) uneven current distribution at the lithium metal interface. Uneven and fluffy lithium plating causes the anode to swell, which reduces the volumetric energy density of the battery cell. External pressure applied to the battery cell can contribute to denser lithium plating, but it has not been shown to eliminate the dendritic fluffy morphology. In addition, external pressure is unfavorable or impractical in many practical applications. External pressure fixtures are undesirable because they require additional volume and weight around the battery cell. Such designs negate the energy density gains that cell designs with lithium metal anodes rather than graphite anodes have traditionally provided. This situation has a greater adverse effect on smaller, typically volume-sensitive consumer electronic devices than on larger cells such as those used in electric vehicles. Larger cells can somewhat withstand a common light-pressure fixture for the entire array of multiple cells, where the weight addition formally assigned to each cell remains limited. However, as described, external pressure has not yet addressed the dendritic fluffy lithium morphology and its resulting performance degradation.
[0015] Protective layers have been added to electrochemical cells between the liquid electrolyte and the lithium metal anode. However, the protective layers known to date still have disadvantages. It is challenging to have a protective layer with sufficient lithium ion conductivity. It is challenging to have a protective layer that is not porous to allow the liquid electrolyte to penetrate too much and eventually reach the lithium metal. It is challenging to have a protective layer that is not too brittle or too hard, which reduces mechanical strength, reduces adhesion, and does not provide flexibility to adapt to the roughness of the lithium surface.
[0016] To address these issues, an electrochemical cell having a novel polymer composite layer specifically formulated for lithium metal anodes and conventional liquid electrolytes is disclosed herein. The polymer composite layer disclosed herein has improved pore control, ionic conductivity, and separator bonding strength when compared to known protective layers. The polymer composite layer disclosed herein has low stiffness, moderate tensile strength, and sufficient elongation to provide the necessary mechanical strength, such as the ability to bend without breaking and the ability to absorb impact energy.
[0017] The electrochemical cell disclosed herein achieves high volumetric energy density and gravimetric energy density using a well-bonded layer stack, which includes an anode current collector, a lithium metal anode, an anode cap layer, a polymer composite layer, and a separator. A specific layer sequence of lithium metal in the form of a lithium metal anode covered with an anode cap layer and protected from liquid electrolyte by a polymer composite layer achieves dense and uniform lithium plating between the anode current collector and the anode cap layer, thereby creating a chemically protected environment without liquid electrolyte during cell cycling. The specific layers and sequences of layers avoid low-density lithium plating, thereby achieving and maintaining high volumetric energy density and long cycle life, all without the need for external pressure fixtures.
[0018] Figure 1 is a schematic diagram of an electrochemical cell 100 as disclosed herein. The electrochemical cell 100 has an anode current collector 102 and a lithium metal anode 104 deposited on the anode current collector 102. An anode capping layer 106 covers the lithium metal anode 104. A polymer composite layer 108 bonds the anode capping layer 106 to a separator 110. The electrochemical cell 100 also has a cathode current collector 112 and a cathode active material 114 deposited on the cathode current collector 112. A liquid electrolyte 116 is represented by an arrow.
[0019] The electrochemical cell 100 disclosed herein provides a solution to the problems discussed herein by using a lithium metal anode that is spatially and therefore chemically separated from a liquid electrolyte via an intervening combination of an anode capping layer 106 and a polymer composite layer 108, wherein the anode capping layer 106 is in direct contact with the lithium metal anode 104 and the polymer composite layer 108 is in direct contact with the liquid electrolyte 116, such as Figure 1 . The polymer composite layer 108 absorbs lithium salts and solvent molecules from the liquid electrolyte 116 during cycling to convert the manufactured polymer composite layer 108 into a polymer electrolyte layer, while limiting the interaction between the lithium metal anode 104 and the solvent and promoting a uniform interface at the anode cap layer 106. The electrochemical cell 100 disclosed herein provides low impedance and uniform bonded solid interfaces. These bonded interfaces avoid the liquid electrolyte interface formed with the lithium metal anode, thereby preventing the uncontrolled growth of low-density, high-volume, dendritic, fluffy lithium metal morphology into the liquid electrolyte space.
[0020] Multiple electrochemical cells 100 can be stacked in a multi-cell design where the current collectors between cells are double-sided. This design distributes half the current collector thickness and weight to adjacent unit cells. Any multiple cells can be incorporated.
[0021] The cathode current collector 112 may be, for example, an aluminum sheet or foil. Other metal and alloy materials are contemplated. The cathode current collector 112 may have a thickness of 6 μm to 12 μm. The cathode active material 114 may include one or more lithium transition metal oxides that may be bonded together using a binder and an optional conductive filler such as carbon black. The cathode active material may have a thickness between 1 μm and 500 μm. The lithium transition metal oxide may include, but is not limited to, LiCoO 2 、LiNiO 2 、LiNi 0.8 Co 0.15 Al 0.05 O 2 、LiMnO 2 、Li(Ni 0.5 Mn 0.5 ) 2 、LiNi x Co y Mn z O 2 , spinel Li 2 Mn 2 O 4 、LiFePO 4 and other polyanionic compounds, as well as other olivine structures, including LiMnPO 4 、LiCoPO 4 、LiNi 0.5 Co 0.5 PO 4 and LiMn 0.33 Fe 0.33 Co 0.33 PO 4 In some embodiments, the cathode active material may consist solely of an electrochemically active material such as sintered LCO. In other embodiments, the cathode active material 114 may include one or both of carbon and a binder.
[0022] The separator 110 is a porous tortuous mechanical layer or membrane that physically separates the cathode active material from the polymer composite layer. The porosity of the separator 110 laminated to the polymer composite layer 108 disclosed herein can be increased from a conventional porosity of about 30%-40% to 60% or more. The thickness of the separator 100 can be between 0.1 μm and 30 μm, and can be composed of a single layer or multiple layers of organic or inorganic materials, such as polyolefins and glass fibers, respectively. The separator can be coated on one or both sides with organic (e.g., polyvinylidene fluoride (PVdF)) and / or inorganic (e.g., magnesium hydroxide (Mg(OH) 2 )) material. The single-sided separator coating can preferably be the coating on the cathode side. Alternatively, the separator coating on the cathode side can be provided by a coating on the cathode instead of a coating on the separator.
[0023] The liquid electrolyte 116 will penetrate the separator and the cathode active material 114 while contacting the cathode current collector 112 and penetrate to the extent described by the polymer composite layer 108, and should be compatible with all four layers under all operating conditions. The liquid electrolyte (although not limiting) may be composed of at least one lithium salt (e.g., lithium bis(fluorosulfonyl)imide (LiFSI)) dissolved in at least one organic solvent (e.g., dimethyl carbonate (DMC)) or an inorganic liquid solvent. The liquid electrolyte 116 may contain at least one ionic liquid (e.g., Py13FSI) and may contain organic and inorganic additives (e.g., bis(2,2,2-trifluoroethyl)ether (BTFE), lithium bis(oxalato)borate (LiBOB)).
[0024] The lithium metal anode 104 can be, for example, lithium metal seeded on the anode current collector 102 during manufacture. The thickness of the lithium metal can be between 0.01 μm and 30 μm. During charging, additional lithium metal is plated onto the lithium metal anode. Alternatively, the electrochemical cell can be an anode-free cell, meaning that the cell is manufactured without a lithium metal anode on the anode current collector, and the lithium metal is deposited between the anode current collector 102 and the polymer composite layer 108 during charging. The anode current collector 102 can be a copper, nickel, or titanium sheet or foil, as non-limiting examples. The thickness of the anode current collector 102 can be between 4 μm and 8 μm.
[0025] The anode cap layer 106 is composed of one or more metals, at least one of which is alloyed with the lithium metal of the anode 104. The thickness of the anode cap layer 106 can be 0.01 μm to 10 μm, and in particular 0.2 μm to 3.0 μm, and is composed of the maximum lithiated alloy of a given metal M that can form an intermetallic compound with lithium. M may include one or more metal elements (ternary, quaternary, pentad, etc.) and may be selected from Sn, Sb, Si, Au, Zn, Al and Mg, as non-limiting examples. M may also contain elements such as Cu, Ti and Ni, which will only form a solid solution with lithium in the case of being binary.
[0026] LiSn is a non-limiting example of an anode cap layer. Galvanic cells are formed when lithium and tin come into contact, which drives alloy formation to a stable state at low temperatures. LiSn also diffuses lithium ions very quickly. LiSn has a thermal conductivity of about 10 -7 cm 2 / s, while LiPON and LiCoO 2 With 10 -9 cm 2 / s and 10 -10 cm 2 / s diffusion coefficient. Both lithium and tin are active materials. Adding an inactive matrix such as Cu, Ti, Ni or NiTi can provide additional stability because these components will not react or move within the layers. Non-limiting examples of anode cap layers include LiSnCu, LiSnTi, LiSnNi and LiSnNiTi. These layer compositions can be formulated so that, for example, the LiSnCu layer can be Cu-rich, or the LiSnCu layer can be coated with a Cu skin near the polymer composite layer 108. Similarly, the LiSnNiTi layer can be, for example, Ni-rich or Ti-rich, or can be coated with a Ni, Ti or NiTi skin near the polymer composite layer 108.
[0027] The anode cap layer is in contact with an excess of lithium metal in the form of a lithium metal anode, and thus adopts the maximum possible lithiated alloy during a given battery cell life. It is empirically found that when the battery cell is charged, lithium atoms are densely and uniformly plated between the anode cap layer 106 and the existing lithium metal with very low impedance, while fusing with the existing lithium metal seed. This location of lithium plating is desirable. The reason why lithium atoms are preferably plated between the anode cap layer and the lithium metal anode, rather than between the anode cap layer and the polymer composite layer, is rooted in the thermodynamic voltage gradient, which does not disappear until the incoming lithium atoms reach the lithium metal anode body. During discharge, the plated lithium is uniformly stripped. The polymer composite layer can be used in an electrochemical cell without an anode cap layer, where the polymer composite layer laminates the separator to the lithium metal or anode current collector. However, the inventors have found that the anode cap layer enables a flatter and denser plating of lithium metal.
[0028] The anode cap layer can be formed by, for example, vacuum depositing M onto a lithium metal anode in an in-situ reaction layer, followed by treatment with, for example, CO 2 There are other methods for forming the anode cap layer, such as, for example, (i) dip coating the lithium metal anode into a solution containing a salt of M, with the lithium metal anode seed reacting with the salt containing M to form Li x M, or (ii) providing a salt of M as an additive in the polymer composite layer, wherein when the polymer composite layer slurry is applied to the lithium metal anode, the lithium metal anode reacts in situ at its surface to form Li x M.
[0029] The polymer composite layer 108 has a cross-linked polymer backbone, polyethylene glycol (PEG), polycaprolactone (PCL), and at least one lithium salt. These can be the only components of the manufactured polymer composite layer 108. It is expected that additional components may be included, but they are not required. Note that during charging and discharging of the battery cell, the polymer composite layer can absorb lithium salts and a limited amount of solvent from the liquid electrolyte 116, while limiting the interaction between the anode and the solvent and promoting a uniform interface at the anode cap layer 106. Except for the casting solvent that evaporates from the manufactured polymer composite layer and is not retained therein, no ionic liquid or other solvent is used or retained in the manufactured polymer composite layer. The thickness of the polymer composite layer 108 may be between about 0.01 μm and 5.0 μm, and more specifically, the thickness is about 1.5 μm to 3.0 μm.
[0030] The cross-linked polymer backbone is a cross-linked polymer having an uncross-linked molecular weight between 100,000 g / mol and 2,000,000 g / mol and accounts for between 40.0 wt % and 90.0 wt % of the manufactured polymer composite layer 108. All ranges herein are inclusive. The polymer backbone is a metal-stable polymer with lithium metal and the anode cap layer and is elastic to dissolution with minimal swelling in the liquid electrolyte 116. The polymer backbone provides a structural matrix to accommodate PEG and PCL and provides bonding (lamination) between the separator and the anode. The polymer of the polymer backbone can be poly(vinylidene fluoride)-co-hexafluoropropylene (PVDF-HFP), poly(vinylidene fluoride) (PVDF), polyethylene glycol dimethacrylate (PEGDMA), polydiallyldimethylammonium bis(fluorosulfonyl)imide (polyDDA FSI), polyvinyl butyral (PVB), poly(urethane acrylate) (PUA), polyethylene glycol (PEO), polyacrylonitrile (PAN), poly(methyl methacrylate) (PMMA) or copolymers thereof. The cross-linked polymer backbone can be one polymer or can be a mixture of more than one polymer. The polymer backbone can be in the form of complete or partial cross-linking, and the cross-linking within the backbone can be achieved by both chemical cross-linking (during synthesis) and physical cross-linking (such as coordination of dissociated lithium salts with fluorine atoms of the polymer).
[0031] PEG has a molecular weight between 20,000 g / mol and 200,000 g / mol and accounts for between 1.0 wt % and 20.0 wt % of the manufactured polymer composite layer 108. PCL has a molecular weight between 20,000 g / mol and 200,000 g / mol and accounts for between 1.0 wt % and 40.0 wt % of the manufactured polymer composite layer 108. Both PEG and PCL can be linear or branched with 3, 4, 6 or 8 arms. The molecular weight range provides a suitable window to enable PEG and PCL to plasticize but not dissolve in the presence of liquid electrolyte 116. The ratio of PCL to PEG in the polymer composite layer is 1:1 to 3:1. The addition of PEG and PCL creates free volume for the lithium salt and a limited amount of solvent from the liquid electrolyte, making lithium salt dissociation and lithium ion conductivity possible, providing additional structural support to the polymer composite layer, and providing additional bonding to the anode and separator.
[0032] The lithium salt can be LiFSI, lithium bis(trifluoromethanesulfonyl)imide (LiTFSI), LiBOB, lithium hexafluorophosphate (LiPF 6 ), lithium tetrafluoroborate (LiBF 4 ) and lithium perchlorate (LiClO 4 ) as a non-limiting example. As a non-limiting example, a dual salt system such as LiFSI and LiBOB can be used. Adding a lithium salt to the polymer composite layer 108 improves ionic conductivity and improves low temperature performance. LiBOB particularly passivates the aluminum cathode current collector to inhibit SFI-Al corrosion. The lithium salt accounts for 30.0 wt % or less of the manufactured polymer composite layer 108.
[0033] Lithium salts are necessary for ion conduction. However, known polymer electrolytes may rely solely on salts for ion conduction and are gated due to the need for large amounts of lithium salts and their inherent pore-forming effects. Higher porosity (20% or greater) and larger pores (maximum pore size of 2 μm or greater) in polymer electrolyte membranes are undesirable because they allow the liquid electrolyte to react with the underlying lithium metal anode. The mechanism for generating large pores is the use of high concentrations of salts and casting solvents. During membrane processing, the solvent evaporates, leaving behind pores filled with salt. To address this issue, additional means of lithium ion conduction independent of lithium salts are sought.
[0034] The addition of PEG enhances ionic conductivity in the polymer composite layer 108. However, the use of PEG alone provides a dense polymer film with no visible pores. Figure 2: is a SEM / EDS image of the surface of a polymer backbone (PVDF-HFP used here) with a molecular weight of 40,000 g / mol 8-arm PEG, showing no visible pores. Without the introduction of some lithium salt, the ionic conductivity is insufficient, and the lack of porosity only enables the addition of very small amounts (less than 5.0 wt%) of lithium salt before uneven, undesirable porosity occurs.
[0035] To address the porosity issue, we found that PCL produces unique pore-forming properties when combined with a polymer backbone, resulting in smaller (≤1.0 μm maximum diameter) and more uniform pores than when lithium salts are added to form pores. Figure 3 is a SEM / EDS image of the surface of a polymer backbone (PVDF-HFP used herein) with a molecular weight of 80,000 g / mol PCL, showing small, uniform pores. PCL and PEG are blended to produce small, uniform pores filled with ion-conductive PEG. With PCL as a pore former and PEG as a pore filler, changing the ratio of PEG and PCL in the polymer composite layer can adjust the porosity of the polymer composite layer. The desired porosity is sufficient to provide the necessary ionic conductivity, but as low as possible to limit the collection of liquid electrolyte solvents. The polymer composite layer 108 disclosed herein has a porosity between 1.0 wt % and 10.0 wt %, more particularly between 1.0 wt % and 8.0 wt %, and more particularly between 1.0 wt % and 5.0 wt %.
[0036] In the case of using PEG for ionic conductivity, the amount of lithium salt required to achieve overall ionic conductivity in the polymer composite layer can be reduced. For example, the ratio of lithium salt to the sum of the cross-linked polymer backbone, PEG and PCL is less than 0.4:1.0, and more particularly 0.2:1, compared to a ratio of lithium salt to polymer of 1.1:1.0 in known polymer electrolyte layers. Figure 4 and Figure 5 are SEM / EDS images illustrating the effect of increasing lithium salt concentration on pore size and uniformity. Figure 4 and Figure 5 is an image of the surface of the polymer composite layer before bonding with the separator. The polymer composite layer has a total of 20 wt% PEG and PCL and 80 wt% PVDF-HFP, and the ratio of PCL to PEG is 3:1. Figure 4 In the case of lithium salt, the lithium salt accounts for 17.0 wt% of the polymer composite layer, resulting in a porosity of 8.0%, while in Figure 5 In the case of PEG and lithium salt, both contribute to the ionic conductivity, the lower concentration of lithium salt achieves an ionic conductivity of ≥ 0.6 × 10 -4 S / cm-1 The polymer composite layer 108. The polymer composite layer acts as a protective layer to block the contact between the liquid electrolyte and the lithium metal anode, thereby reducing or preventing the continuous reaction between the electrolyte and the lithium metal. The polymer composite layer is used as an additional electrolyte layer because the polymer composite layer is lithium ion conductive, thereby promoting uniform lithium distribution and plating at the electrode interface.
[0037] The combination of PEG and PCL has an additional synergistic effect. PEG is more polar than PCL, allowing the polarity of the polymer composite layer to be tuned by varying the ratio of PEG to PCL.
[0038] PCL does not form a separate melting peak / crystalline phase and will integrate with the polymer backbone and lithium salt system. PEG forms a separate crystalline phase because its polarity is significantly different from that of the polymer backbone. The blending of PEG and PCL reduces the crystallinity of PEG, thereby enhancing the mobility of the polymer chains and improving the room temperature conductivity of the polymer composite layer. See Figure 6 , which illustrates the crystallinity of PEG, PCL, a mixture of PEG and PCL, and no PEG or PCL. The higher the melting enthalpy, the greater the crystallinity. Crystallinity makes the material strong, but also makes it brittle. The polymer composite layer disclosed herein has the ability to bend without breaking and absorb impact energy.
[0039] The blending of PEG and PCL reduces stiffness, provides moderate tensile strength and longer elongation, and makes the polymer composite layer highly elastic. When the material has higher stiffness, it is harder and has less adhesion. It also lacks the flexibility to adapt to the roughness of the lithium surface. The polymer composite layer disclosed herein has lower stiffness, moderate tensile strength and longer elongation, thereby providing an excellent bonding material to attach the separator to the anode. Fig. 7A and Figure 7B The elastomeric properties of polymer films containing PEG alone, PCL alone, polymer backbone only, and blended PEG and PCL are illustrated. The elastomeric properties of blended PEG and PCL are shown with a low evolution slope, which reflects its lower stiffness and high elongation at break.
[0040] The polymer composite layer is used to laminate or bond the anode (whether it is the anode cap layer or lithium metal) to the separator, thereby providing strong adhesion between the layers. The internal pressure provided by bonding to the lithium metal is conducive to dense lithium plating under low or no external pressure. The combination of the polymer backbone, PEG and PCL provides excellent bonding strength between the anode and the separator, with a peel strength of more than 60N / m and even a peel strength of 70N / m using a 7-day LE immersion test of the anode, polymer composite layer and separator. In order to achieve this strong bond, the polymer composite layer slurry is cast onto the anode cap layer (or cast onto the lithium metal of the anode if there is no cap layer) before the separator is placed in the slurry before the slurry is dried. The resulting bonding strength is a function of the polymer composite layer, the casting solvent and the drying conditions after casting. The casting solvent may be dimethylacetamide (DMAc), dimethylformamide (DMF), N-methyl-2-pyrrolidone (NMP), tetramethylurea (TMU), N,N-diethylacetamide (DEAc), triethyl phosphate (TEP), and mixtures thereof. The casting solvent is not part of the polymer composite layer or electrochemical cell being manufactured.
[0041] The combination of the strong bonding of the separator to the anode and the reduced porosity of the polymer composite layer enables the use of a separator with increased porosity. A separator with a porosity of 60% or more can be used, compared to conventional separator porosities of 40% or less, which reduces internal battery cell resistance. The increased separator porosity also improves the elastic properties of the separator and the layers to which it is bonded, which better accommodates the non-uniformity of lithium plating.
[0042] The polymer composite layer 108 disclosed herein reduces uneven and fluffy lithium plating while reducing or eliminating the external operating pressure requirements for the battery, resulting in stable battery cell performance. The electrochemical battery cell stack design with a polymer composite layer that bonds the separator to the anode allows cycling at 0 psi external operating pressure and C / 3 charging rate. More than 240 cycles are achieved at a discharge capacity greater than 80%, an increase of 60% over conventional lithium battery cell designs.
[0043] Two embodiments of a polymer composite layer 108 made as disclosed herein are provided in the table below.
[0044] Implementation 1 Implementation 2 PVDF-HFP weight% 62.25 56.25 PCL weight % 14.37 12.98 PEG wt% 6.38 5.77 LiFSI weight % 13.79 20.28 LiBOB weight % 3.21 4.73 Total lithium salt weight % 17.0 25.01 PCL to PEG ratio 2.25:1 2.25:1 Ratio of lithium salt to total polymer 0.2:1 0.33:1 Porosity 8% 10%
[0045] It should be understood that the terms used herein are only for the purpose of describing specific embodiments and are not intended to limit the scope of the present disclosure. It should be noted that, as used herein and in the appended claims, the singular forms "a", "an" and "the" include plural references unless the context clearly dictates otherwise. Thus, for example, reference to "an element" refers to one or more elements, and includes equivalents thereof known to those skilled in the art. Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those of ordinary skill in the art to which the invention belongs.
[0046] While the present disclosure has been described in conjunction with certain embodiments, it should be understood that the present disclosure is not limited to the disclosed embodiments, but on the contrary, it is intended to cover various modifications and equivalent arrangements included within the scope of the appended claims, which scope is to be given the broadest interpretation so as to encompass all such modifications and equivalent structures permitted by law.
Claims
1. A manufactured electrochemical cell comprising: a cathode having a cathode current collector and a cathode active material; an anode, the anode comprising: Anode current collector; lithium metal disposed on the anode current collector; and an anode capping layer on the lithium metal opposite to the anode current collector, the anode capping layer being composed of one or more metals, at least one of the one or more metals being alloyed with the lithium metal; a separator, the separator being located between the cathode active material and the anode; liquid electrolyte; and A polymer composite layer, the polymer composite layer bonding the anode cap layer to the separator, the polymer composite layer consisting of: Cross-linking polymer backbones; Polyethylene glycol; Polycaprolactone; and One or more lithium salts.
2. The electrochemical cell of claim 1 , wherein the cross-linked polymer backbone has an uncross-linked molecular weight between 100,000 g / mol and 2,000,000 g / mol and is selected from the group consisting of PVDF-HFP, PEGDMA, poly-DDA, PVB, PUA, PEO, PAN, PMMA, and copolymers thereof.
3. The electrochemical cell of claim 2, wherein the cross-linked polymer backbone is PVDF-HFP.
4. The electrochemical cell of claim 1, wherein the one or more lithium salts are LiFSI, LiTFSI, LiBOB, LiPF6, LiBF4, or LiClO4.
5. The electrochemical cell of claim 4, wherein the one or more lithium salts are LiFSI and LiBOB.
6. The electrochemical cell of claim 1, wherein the one or more lithium salts comprise 30.0 wt% or less of the polymer composite layer. 7 . The electrochemical cell of claim 1 , wherein the polymer composite layer provides a peel strength between the anode and the separator of greater than or equal to 60 N / m.
8. The electrochemical cell of claim 1, wherein the polyethylene glycol has a molecular weight between 20,000 g / mol and 200,000 g / mol and comprises between 1.0 wt% and 20.0 wt% of the polymer composite layer.
9. The electrochemical cell of claim 1, wherein the polycaprolactone has a molecular weight between 20,000 g / mol and 200,000 g / mol and comprises between 1.0 wt% and 40.0 wt% of the polymer composite layer.
10. The electrochemical cell of claim 1, wherein the polymer composite layer has a porosity of less than 10.0%.
11. The electrochemical cell of claim 1 , wherein the ratio of the one or more lithium salts to the sum of the cross-linked polymer backbone, the polyethylene glycol, and the polycaprolactone is less than 0.4:1.
0.
12. The electrochemical cell of claim 1, wherein the one or more metals of the anode cap layer are Sn and Cu.
13. A lithium metal battery comprising: The electrochemical cell of claim 1, wherein the lithium metal battery has an external operating pressure of 20 psi or less.
14. An electrochemical cell comprising: cathode; Lithium metal anode; a separator, the separator being located between the cathode and the lithium metal anode; Liquid electrolytes; and a polymer composite layer that bonds the lithium metal anode to the separator, the polymer composite layer comprising: Cross-linking polymer backbones; Polyethylene glycol; Polycaprolactone; and One or more lithium salts.
15. The electrochemical cell of claim 14, wherein the polyethylene glycol has a molecular weight between 20,000 g / mol and 200,000 g / mol and comprises between 1.0 wt% and 20.0 wt% of the polymer composite layer.
16. The electrochemical cell of claim 14, wherein the polycaprolactone has a molecular weight between 20,000 g / mol and 200,000 g / mol and comprises between 1.0 wt% and 40.0 wt% of the polymer composite layer.
17. The electrochemical cell of claim 14, wherein the polymer composite layer has a porosity of less than 10.0%.
18. The electrochemical cell of claim 14, wherein the cross-linked polymer backbone is PVDF-HFP.
19. The electrochemical cell of claim 14, wherein the one or more lithium salts are LiFSI and LiBOB.
20. The electrochemical cell of claim 14, further comprising: An anode capping layer on the lithium metal anode, wherein the anode capping layer is composed of one or more metals, at least one of the one or more metals being alloyed with the lithium metal anode.